Capa de revista e produção de sentidos: possibilidades de leitura a partir do acontecimento Serra X Dilma - Vanessa Costa Trindade (2012)
Every seven days, the Brazilian weekly newsmagazines provide verbal and non-verbal texts on their covers to say of mundane issues and events. These covers can be viewed by these publications' regular readers and also by passersby who encounter them in different points of sale throughout the city. Amidst many others, each cover exposed calls for the readers appreciation and tries to convince him to take the book home. But even if he only looks at them, he can assign meanings to what he views using both each cover alone and establishing relationship between it and similar ones published the same week. He can also trigger cover images that were latent in his memory. It is with that in mind that, in this work, we propose to study the magazine cover as a potency of meanings to what is happening in the world, potency that depends on the work of reading to be realized. To develop this idea, we conducted a case study of the coverage of the second round of the 2010 Brazilian presidential elections, held by Veja, IstoÉ, Carta Capital and Época. As a methodological strategy we combined three models coming from different areas: Eisenstein's principle of the ideogram (from Cinema), Animalário do Professor Revillod (from children's literature) and the works of artist Walmor Corrêa (from plastic arts). Together, these models allow us to view the covers published during the period one by one and also in a synchronic set (covers from the same week) and another, diachronic (covers from different weeks). The possibilities of construction of new meanings multiply with each new reading.